2022
DOI: 10.1080/13501763.2022.2125046
|View full text |Cite
|
Sign up to set email alerts
|

The power of ‘weak’ institutions: assessing the EU’s emerging institutional architecture for improving the implementation and enforcement of joint policies

Abstract: European Union (EU) governance faces a fundamental implementation and enforcement dilemma. On the one hand, calls for effective EU policies are manifold and have increased over time. On the other hand, the competence to implement and directly enforce EU policies remains with the member states. To overcome this dilemma, an emerging institutional architecture is taking form in which European Administrative Networks (EANs) and agencies assist the Commission in improving the implementation and enforcement of share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…for alternative solutions (Seddon et al, 2020;Unwin et al, 2020). The growth of the WtE sector offers a promising alternative, but its development has faced significant challenges such as inadequate funds, insufficient expertise, the lack of favorable national policies and legislation, as well as weak enforcement of existing regulations (Asante et al, 2022;Martinsen et al, 2022). To overcome these barriers and solve numerous liabilities related to the environment, especially the mountains of MSW discarded daily, it is necessary to apply facilitating instruments for the social control of public policies, emphasizing strategic guidelines, institutional arrangements, legal aspects and financing mechanisms (Howlett, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…for alternative solutions (Seddon et al, 2020;Unwin et al, 2020). The growth of the WtE sector offers a promising alternative, but its development has faced significant challenges such as inadequate funds, insufficient expertise, the lack of favorable national policies and legislation, as well as weak enforcement of existing regulations (Asante et al, 2022;Martinsen et al, 2022). To overcome these barriers and solve numerous liabilities related to the environment, especially the mountains of MSW discarded daily, it is necessary to apply facilitating instruments for the social control of public policies, emphasizing strategic guidelines, institutional arrangements, legal aspects and financing mechanisms (Howlett, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As outlined by Martinsen et al (2022), EU governance faces a fundamental implementation dilemma: while the demand for EU policies increases, the competence to implement and enforce policies remains with member states, or subnational authorities. The study has implications for the design of European, national and other, philanthropic funding, and for the operationalization of such funding at local and regional level.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, scholars have observed that the European regulatory state and its core non-majoritarian institutions (i.e., EU agencies) often face grave legitimacy issues (Braun & Busuioc, 2020;Rittberger & Wonka, 2011). Recent empirical studies, for instance, suggested that the legitimacy of EU-level agencies can be challenged when they are confronted with dissent, disapproval, or rejection at the national level (Martinsen et al, 2022;Rimkutė, 2018;Schrama, 2022). To illustrate, while the European Food Safety Authority concluded that bisphenol A (a chemical used in plastics) poses no health risk to consumers of any age group, several EU member states restricted the use of bisphenol A in infant feeding bottles based on citizens' concerns, political deliberations, and national epistemic authority (i.e., scientific recommendations of a national regulatory agency).…”
Section: Introductionmentioning
confidence: 99%